Dicksonia timorense (Diksoniaceae), a hemi-epiphytic new species of tree fern endemic on Timor Island, Indonesia - Bayu Adjie; Agung Kurniawan; Norio Sahashi; Yasuyuki Watano (Reinwardtia, 2025)
Dicksonia timorense B. Adjie is described and illustrated as an endemic new species from Timor Island, Indonesia. Population, hemi-epiphytic trait and phylogenetic relationship based on cpDNA sequences are discussed.